IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI DISTRIK KEMBU KABUPATEN TOLIKARA PROVINSI PAPUA - Feri Kogoya; Partino Partino; Untung Muhdiarta (JURNAL KEBIJAKAN PUBLIK, 2020)
Village Fund Allocation is a policy intended to carry out development starting from a small government unit. With the allocation of village funds as a balance fund from the center, it is hoped that it can accelerate development growth at the village level, which is spread across all districts in Indonesia, including Tolikara Regency. For this reason, the purpose of this research is to first examine how the implementation of the Village Fund Allocation policy in 2019 in Tolikara Regency, then to examine the supporting and inhibiting factors in its implementation. The research method used is descriptive qualitative. With the research location focused on Kembu District, with considerations of accessibility. The technique of determining informants is carried out by snowball, for those who are considered to know the research problem. Then, the data collection techniques used were observation and interviews, then the research instruments included, interview guides, and recording devices. Data analysis techniques through the stages of data categorization, data description and data interpretation. The results showed that the implementation of Village Fund Allocation policy in Kembu District when viewed from the aspects of interest, types of benefits, degree of change, position of policy makers, implementers and the resources used were appropriate and right on target. Although experiencing several obstacles such as aspects of management and program implementation. The supporting factors are the high spirit of mutual cooperation in carrying out activities, while the inhibiting factor is the lack of quality of Human Resources in the management of Village Fund Allocation, as well as geographical conditions that affect the distribution